¿Qué representa cambiar el umbral diagnóstico de la hipertensión arterial en Latinoamérica? Guías ACC/AHA 2017 y su aplicación en Perú - Hernández-Vásquez, Akram; Rojas-Roque, Carlos; Santero, Marilina; Ruiz-Maza, Juan Carlos; Casas-Bendezú, Mixsi; Miranda, J. Jaime (Revista Médica de Chile, 2019)
Introduction and Objective. There is little evidence in Latin America about the impact of the ACC/AHA 2017 guideline. Taking as reference the JNC 7 guideline, the objective of our study is to estimate changes in the prevalence of arterial hypertension (HBP) according to socio-demographic characteristics and geographic regions, applying the criteria of the new ACC / AHA guide 2017. Methods. Cross-sectional study of the Demographic and Family Health Survey conducted in Peru in 2017. Standardized weighted hypertension prevalence’s were estimated for the WHO population according to both guidelines, and absolute differences with 95% CI. Results. We included 30 682 people aged 18 years and over, with an average age of 42.3 years, 51.1% women. The standardized prevalence of HBP for 2017 according to JNC 7 was 14.4% (95% CI: 13.8-15.1) and according to ACC / AHA 2017 it was 32.9% (95% CI: 32.0-33.7), so the prevalence increase is 18.5 percentage points, being higher in males than females (24.2 vs. 12.9 respectively). In people with obesity and / or who consume tobacco, the increases were higher (24.3 and 24.1 percentage points respectively). In the regions of Tacna, Ica and Metropolitan Lima, the increase, in comparison with the JNC 7 guidelines, overcome the national average (22.4, 20.7 and 20.4, percentage points, respectively). Conclusions. Considering the context of a Latin American country and knowing the epidemiology of hypertension in Peru, the potential adoption of the ACC/AHA 2017 guidelines for the prevention, detection, evaluation, and management of hypertension should be accompanied by an evaluation of the impact at the individual, system and social level.